Electric Vehicle Fast Charger Planning for Metropolitan Planning Organizations: Adapting to Changing Markets and Vehicle Technology. Issue 1 (January 2015) - Ji, Wei; Nicholas, Michael; Tal, Gil
Presented is a tool to estimate fast charger demand and sample results on a current and future battery electric vehicle (BEV) scenario. The results highlight the data and methods needed to plan for fast charger demand. To plan for existing BEVs, origin and destination data are necessary for identifying which traffic is relevant to assess fast-charging demand. Also, as the battery size for BEVs increases, demand shifts from primarily inside metro areas to long-distance corridors outside metro areas. The sample results show the interactions of battery size, frequency of charging, and energy needed per charge. Although energy per charge increases with battery size, overall electricity demand per vehicle decreases with larger batteries.